Deploying Educational Roaming (eduroam) in a Rural Research Institution in Rakai, Uganda; Challenges and Lessons Learned - Ssentongo, Lloyd; Kimera, Rodgers; Kakeeto, Ben; Mubiru, Moses; Moyer, Brain K; Economou, Matthew; Whalen, Christopher J; Tartakovsky, Michael (My University, 2016)
The NIAID International Center for Excellence in Research (ICER) in Uganda, RHSP (Rakai Health Sciences Program) recently deployed the eduroam service at the laboratories and offices in the village of Kalisizo and the main offices at Entebbe. Eduroam is a global framework to allow academics and researchers to have wireless access from any participating institution. An acronym for educational roaming, eduroam is a user friendly solution that provides a common WiFi network (SSID) at all participating universities and research organizations. Unlike the typical model of “guest” networks, this system provides a real identity to which network administrators and security staff can map both traffic and activity. There are clearly defined structures in place for reporting inappropriate activity to the home institution. The deployment of eduroam by the Office of Cyber Infrastructure and Computational Biology at the Ugandan ICER faced challenges and taught the team a number of lessons. The implementation began May 2016 in a test environment and was one of the first organizations to do so in Uganda. We share our experience in as far as challenges and lessons learnt.
Keywords: Eduroam; Rural Research Institution; Uganda